BARRIERS IN INTERVENTION CHARACTERISTICS OF CLUSTER HOSPITAL (CH) IMPLEMENTATION IN MALAYSIA: AN EXPLORATORY STUDY - Khairul Anuar, Ili Liyana; Mohd Kamil, Nik Dewi Delina Nik; Noris, Nur Jihan; Bakit, Pangie Anak; Jie, Ng Rui; Ibrahim, Nor Hayati (LIFE: International Journal of Health and Life-Sciences, 2021)
To address an imbalance between congested specialist hospitals and underutilised district non-specialist hospitals, Ministry of Health Malaysia introduced Cluster Hospital (CH) in 2014. Following successful implementations from countries with similar healthcare system such as Hong Kong, and Australia, CH merges hospitals to establish an integrated network of specialist and non-specialist hospitals through shared resources, streamlined services and care coordination. A qualitative study was conducted to explore perceived barriers and boosters towards CH implementation and its sustainability among healthcare providers via semi-structured focus group discussions and in-depth interviews with purposefully selected respondents from the first six CHs. An Interview protocol was developed based on Consolidated Framework for Implementation Research (CFIR) covering five domains; intervention characteristics, outer setting, inner setting, characteristics of individuals, and process. This paper will only highlight the perceived barriers in the intervention characteristics domain. A total of 274 participants from varying professions were interviewed. Interviews were audio-recorded, transcribed and thematic analysis was performed. In this domain, barriers to implementation were found within three constructs; complexity, design quality & packaging, and cost. Issues highlighted include intervention was designed with vague guidelines & policies, distance and travel costs within a CH, medical record safety, huge capital and operating cost involved. It was found that adaptation of evidence-based interventions needs to take into account the local context of an organisation for the implementation to be successful and produce desired outcomes. Thus, these perceived barriers raised by ground-level implementers should be considered and acted upon when strategising towards CH sustainability.